2004
DOI: 10.1074/jbc.m311572200
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Factor from Thermus thermophilus Is a Zn2+-dependent Chaperone

Abstract: The ribosome-associated chaperone trigger factor (TF) of Escherichia coli interacts with a variety of newly synthesized polypeptides to assist their correct folding. Here, we report that the TF of thermophilic eubacterium, Thermus thermophilus, arrested spontaneous folding of green fluorescent protein by forming a 1:1 binary complex. The complex was isolable by gel-filtration but was shown to be dynamic because green fluorescent protein was released by ␣-casein in large excess. Unexpectedly, EDTA completely ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…In this position, surrounded on one side by the M domain of the SRP and on the other side by the hydrophobic cleft of the trigger factor, the nascent chain can be monitored by both factors ( Figures 4E and 4F and step B in Figure 5). Such a model is consistent with previous biochemical data suggesting that, instead of promoting protein folding, TF delays it, both upon dilution from denaturant (Suno et al, 2004) as well as during de novo protein synthesis, in vitro and in vivo (Agashe et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In this position, surrounded on one side by the M domain of the SRP and on the other side by the hydrophobic cleft of the trigger factor, the nascent chain can be monitored by both factors ( Figures 4E and 4F and step B in Figure 5). Such a model is consistent with previous biochemical data suggesting that, instead of promoting protein folding, TF delays it, both upon dilution from denaturant (Suno et al, 2004) as well as during de novo protein synthesis, in vitro and in vivo (Agashe et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Thermus thermophilus (15), Hsp70 and Hsp100 chaperones (16) and the chaperonins (17). Here, we describe investigation of the folding of guanidine-denatured GFPuv in the presence and absence of Escherichia coli TF.…”
mentioning
confidence: 99%
“…GroEL and trigger factor represent two out of the four intracellular molecular chaperones in E. coli (Houry 2001). Trigger factor has been reported to be regulated by Cd(II) stress (Ferianc et al 1998), and a homolog in Thermus thermophilus (Suno et al 2004) has recently been reported to bind Zn(II). Lastly, the most abundant protein in E. coli, TufB (Weijland et al 1992), was upregulated along with the ribosomal protein L9 (Herbst et al 1994) and carbamoyl phosphate synthase (CarB) (Rubino et al 1987).…”
Section: D Gels Of E Coli Culturesmentioning
confidence: 99%